Biomethane—Future Trends - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. Given global greenhouse gas reduction pressures and incentives for renewables there are strong forces supporting the future growth of the global biomethane industry. This chapter deals with future technologies and uses of biomethane. Developments in improving anaerobic digesters, such as acid-phase digesters, are examined. Future sources of biogas from second-generation biofuels, including from algae and lignocellulosic biomass, are discussed. Following that discussion, technologies that could be used to improve the upgrading of biogas are included. These include energy-efficient methods such as in situ methane and enzyme enrichment. Future methods for storing biomethane, such as adsorbed natural gas and liquefied biomethane, are discussed. The book finishes with a recommended pathway for future biomethane development.